Decoding the Genetics of Inherited Retinal Diseases in Ireland - DOCKERY, ADRIAN (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2019)
Title: Decoding the Genetics of Inherited Retinal Diseases in Ireland Short Description: The Target 5000 study aims to provide genetic testing for the estimated 5,000 people in Ireland who are affected by a genetic retinal condition. Currently, nearly 1000 patients in Ireland have been sequenced and approximately 80 novel candidate variants have been discovered. Purpose: While clinical trials are in progress for patients with inherited retinal degenerations (IRDs), many such trials require patients to have a known causative mutation to participate in these trials. The Target 5000 research project aims to genetically characterise the estimated 5,000 people in Ireland affected by IRDs. Approach: The IRD patient cohort used in the study has been obtained via a collaborative network of ophthalmologists whereby if an IRD is suspected, given consent, a DNA sample is taken and provided to a central laboratory for genetic analysis. The study seeks to detect previously identified, together with as yet undiscovered, pathological mutations in a panel of known retinal degeneration genes utilizing target capture next generation sequencing (NGS). Where a candidate variant is identified by NGS, additional family members are recruited to verify the appropriate presence and segregation of the variant with the relevant condition. The study to date includes data from nearly 1000 IRD patients. Results: To date, nearly 1000 patients from the Irish IRD population have been sequenced for 254 genes, providing real insights into the genetic architecture of IRDs in Ireland. Target 5000 offers not only a chance to discover new relevant and pathogenic mutations but is vital to providing patients with information regarding the underlying genetic pathogenesis of their disease. Over 80 novel IRD mutations have been discovered to date, this includes several novel large structural variants such as inversions and deletions spanning several kilobases. The findings have also proved useful in the clinical setting where candidate variants have helped to resolve some previously ambiguous disease phenotypes. The study has also led to the identification of several actionable variants in our cohort where there is active recruitment for natural history studies or clinical trials of new therapeutics. Conclusions: The aim of the study is to genetically characterise patients with IRDs in Ireland and in principle potentially enable clinical trials to be more accessible for some patients analysed where appropriate. Thus far, during the study, genetic analysis of IRD patients has helped to resolve ambiguous phenotypes and to identify causative mutations in nearly 70% of cases. The continuous growth of the cohort has enabled us to better analyse the sequencing data and interpret the potential pathogenicity of novel variants when detected. In addition to this, the growing body of data from NGS studies of IRDs globally should facilitate better correlations between genotype and phenotype and further refine methods for diagnoses and prognoses.
APPROVED
Keywords: Genetics; Retinal; Blindness; Sequencing; NGS; Health Research